Significant Release of Dissolved Inorganic Nutrients From the Shallow Submarine Volcano Tagoro (Canary Islands) Based on Seven-Year Monitoring - González-Vega, Alba; Fraile-Nuez, Eugenio; Santana-Casiano, J. Magdalena; González-Dávila, Melchor; Escánez-Pérez, José; Gómez-Ballesteros, María; Tello, Olvido; Arrieta, Jesús M. (Frontiers in Marine Science, 2020)
Tagoro, the shallow submarine volcano that erupted south of El Hierro (Canary Islands, Spain) in October 2011, has been intensely monitored for over 7 years, from the early eruptive stage to the current degassing stage characterized by moderate hydrothermal activity. Here, we present a detailed study of the emissions of inorganic macronutrients (NO2-+NO3-, PO4, and Si(OH)4) comprising a dataset of over 3300 samples collected through three different sampling methodologies. Our results show a significant nutrient enrichment throughout the whole studied period, up to 8.8-fold (nitrate), 4.0-fold (phosphate) and 16.3-fold (silicate) in the water column, and larger enrichments of phosphate (10.5-fold) and silicate (325.4-fold), but not of nitrate, in the samples collected directly from the vents. We also provide some preliminary results showing ammonium (NH4+) concentrations up to 1.97 µM in the vent fluids as compared to 0.02 µM in the surrounding waters. Nutrient fluxes from the volcano during the degassing stage were estimated as 3.19 ± 1.17 mol m-2 yr-1 (NO2-+NO3-), 0.02 ± 0.01 mol m-2 yr-1 (PO4), and 0.60 ± 1.35 mol m-2 yr-1 (Si(OH)4), comparable to other important nutrient sources in the region such as fluxes from the NW-African upwelling. Nutrient ratios were affected, with a minimum (NO3-+NO2-):PO4 ratio of 2.36:1; moreover, a linear correlation between silicate and temperature allowed to use this nutrient as a mixing tracer. This study is bound to shed light on how shallow hydrothermal systems impact the nutrient-poor upper waters of the ocean.